Comparing Teacher Strategies in Encourage Speaking English in Rural and Urban Areas - Duratun Nasekhah; Girindra Putri Dewi Saraswati (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2026)
This study aims to compare the strategies used by pre-service English teachers in encouraging students to speak English in urban and rural schools in Semarang, as well as to identify challenges faced in both contexts. Using a qualitative research approach, the study involved four pre-service English teachers participating in a teaching internship program, consisting of two participants from urban schools and two from rural schools. Data were collected through interviews and document analysis, including lesson plans and teaching materials, and analyzed using thematic analysis to identify patterns related to speaking strategies and contextual challenges. The findings indicate that pre-service teachers in rural schools tend to employ simpler and more supportive strategies, such as group work, language games, short conversations, and question-and-answer activities, with a focus on building students’ confidence and reducing anxiety caused by limited vocabulary and minimal exposure to English outside the classroom. In contrast, pre-service teachers in urban schools employ more varied and structured strategies, including discussions, presentations, role-play, think-pair-share, and digital media to promote active participation. Despite contextual differences, both learning environments face similar challenges, particularly low student confidence. This study concludes that speaking instruction is context-dependent and requires pre-service teachers to adapt strategies effectively in classrooms